Developing Adult Sepsis Protocol to Reduce the Time to Initial Antibiotic Dose and Improve Outcomes among Patients with Cancer in Emergency Department - Mustafa Z Bader; Abdullah T Obaid; Hisham M Al-Khateb; Yazeed T Eldos; Moath M Elaya (Elsevier, 2020)
Objective: Sepsis is a common cause of noncancer-related deaths among oncology patients. Delay in the initiation of efficient antimicrobial therapy will decrease the survival rate. This study aims to develop a sepsis protocol for adult oncology patients to decrease the time needed to receive the initial dose of antibiotic in an emergency department (ED), improve the early recognition of sepsis, and decrease the in-hospital mortality rate due to sepsis. Methods: A quasi-experimental research design was used. A total of 168 participants were assigned into pre- and post-intervention groups (n = 85) and (n = 83), respectively. The quick Sequential Organ Failure Assessment screening tool was used to screen patients in the triage room. Results: There was a significant difference in the proportions of receiving the initial antibiotic dose whether ≤1 h or >1 h between pre- and post-intervention groups. The results also showed that 89.4% of the postintervention group received their initial antibiotic dose in <1 h compared with 10.8% of the preintervention group. The median time needed for administering the initial antibiotic dose was decreased from 95 min to 45 min. The results of the changes in mortality rates are promising as it decreased 11.7% after applying the adult sepsis protocol. Conclusions: Applying an adult sepsis protocol in the ED significantly decreased the time needed to initiate antibiotic treatment. It is recommended to utilize a multidisciplinary and systematic approach in screening and treating sepsis.